(untitled) (Acta Scientiarum. Biological Sciences, 2013)
This study analysed the prevalence of parasitic and fungal infections in rodents in an area of urban expansion, Aracaju, Brazil. Traps were placed in the area from December 2011 to January 2013. Blood samples, faeces and hair were collected from the animals. We collected a total of 47 rodents; 44 were Rattus rattus, and 3 were Mus musculus. Parasitological evaluation revealed the cestode Hymenolepis diminuta infection in both rodent species. The nematodes Aspiculuris tetraptera and Syphacia obvelata were found in M. musculus, and the commensal Entamoeba coli was found in R. rattus. We observed that 69.2% of the R. rattus and 33.3% of the M. musculus were infected with the haemoparasite Babesia sp. The differential leukocyte count revealed normal (72.3%), neutrophilic (15.9%) and lymphocytic (11.4%) profiles. The evaluation showed the following species of fungi in the rodents: Aspergillus sp. (77.1%), Penicillium sp. (28.6%), Cladosporium sp. (14.3%), Mucor sp. (14.3%), Curvularia sp. (8.6%), Acremonium sp. (8.6%), Chrysosporium sp. (2.9%), Syncephalostrum sp. (2.9%), Alternaria sp. (2.9%), Trichophyton sp. (2.9%) and Scopulariopsis sp. (2.9%). The parasites and fungi found in rodents are potentially zoonotic, and the presence of these household animals demonstrates their potential role as reservoirs and disseminators of fungal and parasitic infections.